Research and development towards duty factor upgrade of the European X-Ray Free Electron Laser linac - J. Sekutowicz; V. Ayvazyan; M. Barlak; J. Branlard; W. Cichalewski; W. Grabowski; D. Kostin; J. Lorkiewicz; W. Merz; R. Nietubyc; R. Onken; A. Piotrowski; et al. (Physical Review Special Topics. Accelerators and Beams, 2015)
We discuss the progress in the R&D program for a future upgrade of the European XFEL facility, namely for an operation in the continuous wave (cw) and long pulse (lp) modes, which will allow for significantly more flexibility in the electron and photon beam time structure. Results of cw/lp runs with preseries XFEL cryomodules and status of components needed for the new operation modes are presented here.